Superpagg: Uma Ferramenta Crowdsourcing para Comparação de Preços em Supermercados - Arthur, Paulo Henrique Gouvea; Santos, Bruno Carvalho; Pontes, Leandro Martha; Duarte, Maycon Andrade; Pires, Adonias Pinheiro; Souza, Alan Marcel Fernandes (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2019: Anais Estendidos do XXV Simpósio Brasileiro de Sistemas Multimídia e Web, 2019)
People often try to spend as little as possible when shopping at a supermarket. Many people can not reduce their costs when buying, either because of lack of time to research or because of the wide variety of products and prices. This article presents the Superpagg software, whose main objective is to help people to spend less on purchases in supermarkets by comparing the prices of different products in different supermarkets, so that the user can see where to pay less for the same products, allowing them to make their purchases with more economy. The results obtained were that the information presented by the software, using a limited sampling, is that the consumer saves from 2.01% to 17.64% monthly per product purchased.